The Role of AI-Based Islamic Education in Improving Students' Spiritual Literacy in the Digital Era Study at SMAN 4 Tuban - Fitri Minhatus Saniyah (Ilmina: Journal of Education and Counseling, 2025)
This study aims to analyze the role of Artificial Intelligence (AI)-based Islamic Religious Education (PAI) in enhancing students’ spiritual literacy in the digital era, with a focus on SMA Negeri 4 Tuban. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation involving PAI teachers and students. The findings show that AI has been utilized in the learning process, mainly through digital platforms such as Quizizz, Canva, and Google Workspace, although its use remains at the technical-support level rather than an integrated pedagogical model. Teacher readiness, student familiarity with digital tools, and AI-supported efficiency are identified as supporting factors. However, limited digital competence of teachers, uneven access to devices, unstable internet connectivity, and the risk of misinformation are significant challenges. The use of AI is found to have a more substantial impact on students’ cognitive understanding than on their spiritual literacy, which still requires human guidance, habituation, and exemplary behavior. The study concludes that while AI contributes to improving learning efficiency, it cannot replace the affective and spiritual dimensions essential in PAI learning. Strengthening digital competence and thoughtful integration of AI remains crucial for optimizing its role in developing students’ spiritual literacy.